Impact of Social Media Marketing, Brand Image, And Trust On Purchase Intention Customer Eiger In Labuhanbatu - Hansyah, Praida; Amin, Mhd.; Aprilia, Mutya; Syahputra, Aril Ananda; Hanif, Khairil (Jurnal Manajemen Akuntansi (JUMSI), 2025)
This study aims to analyze the influence of social media marketing, brand image, and trust on the purchase intention of Eiger customers in Labuhanbatu. A quantitative approach using a survey method was employed, with data collected through questionnaires distributed to 100 respondents who are Eiger consumers. Data were analyzed using multiple linear regression analysis. The results show that all three independent variables social media marketing, brand image, and trust have a significant partial and simultaneous influence on purchase intention. The regression coefficients are 0.245 for social media marketing, 0.181 for brand image, and 0.242 for trust, with significance values below 0.05. The R Square value of 0.410 indicates that the model explains 41% of the variation in purchase intention. These findings suggest that in the context of local retail marketing, integrating social media strategies, strengthening brand image, and building consumer trust are essential for increasing purchase intention.